Some aspects of consideration of cases concerning decisions, actions or inaction of the body of the state executive service body, private executor in administrative proceedings - Verbitska, Mariana; Balyk, Viktoriia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2022)
The article is devoted to some aspects of consideration of cases concerning decisions, actions or inaction of the body of the state executive service, private executor are investigated. Particular attention is paid to the delimitation of jurisdiction and the peculiarities of the procedure. The main problems related to the application of procedural law to decisions, actions or omissions of the state executive service, a private executor in administrative proceedings are highlighted. Attention is focused on the relevance of this topic in the present. The conclusions state that in case of violation of rights, freedoms and interests a person has the right to appeal to the court of first instance to appeal against decisions, actions or omissions of the state executor and other officials of the state executive service, state executive service, private executor. However, in order for the parties, other participants and persons to exercise their above-mentioned rights, the legislator should systematically approach the issue of jurisdiction of this category of disputes in view of the Supreme Court practice, as well as unify the rules of appealing decisions state executive service, private executor, so that the law was as accessible, clear and understandable as possible, including for the average citizen.